2006
DOI: 10.1080/03079450600711029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of heterophil functions of modern commercial and wild-type Rio Grande turkeys

Abstract: The purpose of the present study was to measure any functional differences in peripheral blood heterophils isolated from a commercial turkey line to wild-type Rio Grande turkeys. The phagocytosis of Salmonella enteritidis, oxidative burst (OXB) and degranulation (DGR) were used as parameters of heterophil functional efficiency in these studies. Blood was collected and heterophils isolated from each line of turkeys at days 4, 7, and 14 post-hatch. On days 4 and 7 post-hatch, heterophils from Rio Grande turkeys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…However, there is some experimental evidence that long-term selection for improved performance (i.e., superior growth rate, carcass weight, and other production traits), may be accompanied by negative physiological consequences, for instance by disadvantageous changes in immune functions and lower resistance of animals to pathogenic factors (Qureshi and Havenstein, 1994;Li et al, 1999;Kramer et al, 2003;Huff et al, 2005;Genovese et al, 2006). For example, in comparing the immunocompetence of fastgrowing commercial broilers (Ross 308) and a line of chickens unselected over decades, it was found that long-term genetic selection for increased growth performance adversely affected the adaptive arm of immune response, i.e., antibody production against sheep red blood cells (SRBC) and lymphoid organ relative weights (Cheema et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some experimental evidence that long-term selection for improved performance (i.e., superior growth rate, carcass weight, and other production traits), may be accompanied by negative physiological consequences, for instance by disadvantageous changes in immune functions and lower resistance of animals to pathogenic factors (Qureshi and Havenstein, 1994;Li et al, 1999;Kramer et al, 2003;Huff et al, 2005;Genovese et al, 2006). For example, in comparing the immunocompetence of fastgrowing commercial broilers (Ross 308) and a line of chickens unselected over decades, it was found that long-term genetic selection for increased growth performance adversely affected the adaptive arm of immune response, i.e., antibody production against sheep red blood cells (SRBC) and lymphoid organ relative weights (Cheema et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in the current study, the observed increase in heterophil function is likely to be a result of increased activation of PTK signalling and elevated p38 levels, suggesting a connection between these signalling pathways and PMN functional efficiency in both chickens and turkeys. The ERK MAPK family was not a differentiating factor between the two lines of chickens tested in the current study, yet in turkeys there is a differential response (Genovese et al, 2006) suggesting that ERK contributes, in part, to the functional efficiency of heterophils from wild-type turkeys but not in the broiler lines we tested. Also, a study using heterophils isolated from 1-day-old Leghorn chickens (egg layers) shows that the bacterial components lipopolysaccharide and flagellin increase ERK activity .…”
Section: Discussionmentioning
confidence: 60%
“…The results showed there were no obvious deletions in any specific signalling pathway(s) between heterophils from lines A and B, and that the differences are more likely attributable to slight differences in the early MAPK signalling events. A study by Genovese et al (2007) compared PTK, ERK, and p38 activity in heterophils isolated from wild-type and commercial large-bodied turkeys and showed significantly higher levels of activity for all three signalling components in the wild-type birds over the commercial variety, which corresponds to increased heterophil function (Genovese et al, 2006). As demonstrated in the current study, the observed increase in heterophil function is likely to be a result of increased activation of PTK signalling and elevated p38 levels, suggesting a connection between these signalling pathways and PMN functional efficiency in both chickens and turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Selective breeding programs (especially in poultry) have dramatically improved carcass characteristics desired by consumers (e.g., breast size in broilers), but genetic selection focused on this single phenotypic trait has, in some cases, reduced the strength and responsiveness of the immune system [ 7 , 74 ]. Methods that improve the functionality of the innate immune system can be highly influential, conferring upon the host a type of “trained immunity” against a broad spectrum of pathogens [ 75 ].…”
Section: Individual Seminar Sessionsmentioning
confidence: 99%